Impact of Digital Technology Usage on Children’s Behavior: A Case Study - Lamsal, Asmita; Gurung, Golman (Nepalese Journal of Business and Management Studies, 2022)
In the era of digital technology, various technologies have been used with the change in time and found to be updated. But there are limited research updates related to the impact of digital technology today on children. This study aims to examine the effect of digital technology usage on children’s behavior. Piaget’s theory of cognitive development is used in the study. Children’s behavior talks about aggression, slow responsiveness, socially inactive, and anxiety. The research study was designed to identify the impacts of digital technology usage on children’s behavior at Ramailo Pathshala School, Jarankhu, Kathmandu. Only one variable is taken as an independent variable in the study, i.e., digital technology usage. Here, children’s behavior is taken as the dependent variable. Data collection was done with the help of a structured questionnaire which was distributed among 125 students, out of which 105 students represent the sample size. Descriptive, relational, and causal research designs were used in this study and correlation and regression were used as major statistical tools. The findings revealed that digital technology usage significantly affects children’s behavior